Autoimmune fibroinflammation in IgG4-related ophthalmic disease: TLR8-dependent signaling pathways and fibrotic remodeling revealed by proteomic profiling - Ma, Yingxue; Song, Dejuan; Xu, Chuanjie; Li, GuangYu (Frontiers in Immunology, 2026)
BackgroundImmunoglobulin G4-related ophthalmic disease (IgG4-ROD) is an immune-mediated ocular condition characterized by tumefactive lesions with IgG4+ plasma cell infiltration, and commonly affecting the lacrimal gland, extraocular muscles, and trigeminal nerves.The precise pathogenesis of IgG4-ROD remains unclear. Elucidating its molecular mechanisms is crucial for the development of targeted molecular therapies.MethodsTo investigate the molecular pathogenesis of IgG4-ROD, we conducted a case-controlled study involving 15 patients who presented at the Second Hospital of Jilin University between 2021 and 2022. In accordance with the comprehensive diagnostic criteria for IgG4-related disease (IgG4-RD) established in 2011, participants were stratified into three distinct cohorts based on lacrimal gland histopathological findings: confirmed IgG4-ROD, suspected IgG4-ROD, and a control group. We then utilized 4D-Fast DIA technology to acquire proteomic profiles from the lacrimal gland biopsies, with rigorous bioinformatics methodologies employed to process and interpret these data, focusing on the differential protein expression patterns across the groups, aiming to identify signaling pathways that are significantly associated with IgG4-ROD.ResultsThe comparative analysis of clinical characteristics, imaging features, and histopathological findings among the control group, patients with suspected IgG4-ROD, and diagnosed patients revealed a progressive trend towards more severe pathology. Principal component analysis (PCA) and Pearson correlation heatmaps indicated that the profiles of differentially expressed proteins in lacrimal gland samples from the suspected and diagnosed groups were highly similar, suggesting that the patients from these two groups may belong to the same population. Further analysis of protein expression changes across the three groups revealed significant enrichment in pathways related to asthma, Th1 and Th2 cell differentiation, and other relevant signaling pathways. Notably, Toll-like receptor (TLR), NF-κB, Wnt, and PI3K-AKT signaling pathways were prominently activated. In the diagnosed group, proteins such as MMP7, POSTN, and CD163 exhibited characteristic high-level expression. Furthermore, compared with the suspected group, the diagnosed group showed significant downregulation of proteins related to elastin fibers, indicating a more severe degree of fibrosis in the lacrimal gland tissues. Additionally, the diagnosed group exhibited a significant decrease in proteins associated with lacrimal secretion, suggesting impaired function of lacrimal gland. We also observed a notable upregulation of TLR-8-related proteins in both the suspected and diagnosed groups, implying that the TLR signaling pathway may be closely related to this disease.ConclusionsProteomic analysis of lacrimal gland samples from the diagnosed, suspected, and control groups suggests that patients with suspected IgG4-ROD may be part of the same population as diagnosed patients. In the diagnosed group, the lacrimal gland tissue displayed more severe fibrosis and a significant loss of lacrimal secretion function. This study postulates that the TLR - 8/IRAK4/NF - κB pathway may contribute to the molecular pathogenesis of IgG4 - ROD by promoting tissue fibrosis. Proteins such as MMP7, POSTN, and CD163 could potentially serve as molecular markers for the early diagnosis and potential therapeutic targets of IgG4 - ROD. Based on these findings, proteomics offers significant advantages in the molecular diagnosis of IgG4 - ROD and should be regarded as a crucial tool in the diagnosis of this disease.